Norepinephrine regulates calcium signals and fate of oligodendrocyte precursor cells in the mouse cerebral cortex - Frederic Fiore; Khaleel Alhalaseh; Ram R. Dereddi; Felipe Bodaleo Torres; Ilknur Çoban; Ali Harb; Amit Agarwal (Nature Communications, 2023)
Abstract Oligodendrocyte precursor cells (OPCs) generate oligodendrocytes, contributing to myelination and myelin repair. OPCs contact axons and respond to neuronal activity, but how the information relayed by the neuronal activity translates into OPC Ca2+ signals, which in turn influence their fate, remains unknown. We generated transgenic mice for concomitant monitoring of OPCs Ca2+ signals and cell fate using 2-photon microscopy in the somatosensory cortex of awake-behaving mice. Ca2+ signals in OPCs mainly occur within processes and confine to Ca2+ microdomains. A subpopulation of OPCs enhances Ca2+ transients while mice engaged in exploratory locomotion. We found that OPCs responsive to locomotion preferentially differentiate into oligodendrocytes, and locomotion-non-responsive OPCs divide. Norepinephrine mediates locomotion-evoked Ca2+ increases in OPCs by activating α1 adrenergic receptors, and chemogenetic activation of OPCs or noradrenergic neurons promotes OPC differentiation. Hence, we uncovered that for fate decisions OPCs integrate Ca2+ signals, and norepinephrine is a potent regulator of OPC fate.